Namibian school principals' perceptions of their management development needs - Kapapero, Fanuel (Rhodes University, Faculty of Education, Department of Education, 2008)
The Namibian education system is at the crossroads as a result of the demands of the Education and Training Sector Improvement Programme (ETSIP), a programme initiated by the Government to address shortcomings in the education and training sector. ETSIP requires that school principals play a much more significant role to realize the goal of quality education, which is one of the major goals of education reform. In view of the ever-increasing responsibilities of the principals for ensuring the quality of education, the need for management development has become more apparent. Although management development for principals in the African context is a recent phenomenon, it has been a subject of extensive research over the years in many developed countries. The findings of these studies suggest that it has the potential to improve the quality of school leadership and ultimately lead to school improvement. In Namibia, literature suggests that little has been done to determine the needs of school principals with regards to their management development. This study therefore seeks to address that need. The study is situated in the interpretive research paradigm whose central purpose is to interpret and understand the phenomenon through the perceptions and experience of the participants. Data were collected by means of semi-structured interviews and document analysis. The findings generally suggest that principals perceive management development as vehicle to empowerment and capacity building. The findings further suggest that principals would prefer management programmes that are more experienced-based and offer opportunities for reflection. The findings also brought to light the aspect of monitoring and support as a critical element in the success of management development programmes. As far as the management development needs of school principals are concerned, the findings highlighted the following needs: the need to be trained on how to manage change which include the new curriculum and policies, training in information communication and technology and training in the management of human and financial resources which include instructional leadership and budgeting.
Keywords: School principals -- Self-rating of -- Namibia; School principals -- Rating of -- Namibia; School principals -- Management -- Namibi; School principals -- Development -- Namibia; School management and organization -- Namibia; Educational leadership -- Namibia; School supervision -- Namibia